Two strip flap technique for total lower lip reconstruction: case report - Qi, Wenli; Xiao, Xinyue; Tong, Jing; Guo, Nengqiang (Frontiers in Medicine, 2025)
BackgroundMalignant tumor removal can cause extensive lower lip tissue loss, affecting speech, expression, and swallowing functions.MethodsWe describe our experience with two cases using a modification of the nasolabial flap technique for total lower lip reconstruction. This approach employs two long strip-shaped flaps rotated to reconstruct the entire lower lip, which helps mitigate functional limitations caused by microstomia.ResultsTwo patients underwent successful reconstruction with normal lip function, no microstomia, and restored eating ability. Partial vermillion remained visible with good lip shape. No complications occurred during follow-up (12 months), with satisfactory oral competence and no drooling or speech impairment.ConclusionThis surgical method has a certain improvement in microstomia compared with the traditional surgery used for similar lower lip defects, while achieving satisfactory functional and aesthetic outcomes. The technique represents a preliminary technical note for total lower lip reconstruction with favorable outcomes in our limited series.